Urolithiasis-related ureteric intussusception: A rare case report - Hashim Homaida; Ibrahim A. Khalil; Ahmed Haroon; Jamil Ahmad; Khalid Mahmoud; Hosam Tawfik; Abdelfattah Omran; Abdulqadir Alobaidy; Abdullah A. Al-Ansari (Urology Case Reports, 2024)
Ureteral intussusception is a rare condition that historically occurs as a complication of ureteral neoplasms or iatrogenic endoscopic procedures. Although the exact mechanism of ureteral intussusception is unclear, most reported cases are due to leading points as malignant or benign masses. Urolithiasis related is rarely reported and can be challenging in stone management as it might decrease the spontaneous stone passage rate. In addition, it will increase the complexity of the endoscopic stone management. We present the second reported case of urolithiasis-related ureteric intussusception presented with urosepsis due to obstructive uropathy, successfully managed by an endourological approach.